The Role of Multi-Media Approach in Narrowing the Kap-Gaps Among the Farmers of the Strategic Extension Campaign in Muda Irrigation Scheme in Malaysia - Herianto, Ageng Setrawan (1997)
The objectives of this study were: (1) to compare the level of Knowledge Attitude and Practice (KAP) on the Brown Plant Hopper (BPH) control management technology between the farmers with low and high socio-economic status (SES) in the Muda Agricultural Development Authority (MADA) area before and after the Strategic Extension Campaign (SEC); (2) to determine the change in KAP-gaps on the BPH control management technology among those farmers before and after the SEC; (3) to determine the relationship between farmer's characteristics and social activities, and the KAP-level before the SEC; (4) to determine the relationship between farmer's characteristics, social activities and rimlti-media factors in the SEC and the KAP-Ievel after the SEC; and (5) to predict the KAP-Ievel based on the KAP-equation of low and high-SES farmers in the MADA area, Malaysia.The MADA had launched the SEC on BPH control management based on a KAP-survey. This study was designed as Pre and Post Campaign study. The KAP survey results as the secondary data of the study was the benchmark data of the precampaign study. The study evaluated effects of the campaign. A sample of 189 farmers were selected by using the stratified sampling procedures. Data were gathered by means of personal interviews using structured questionnaire and analysed using the SPSS for Window version 7.5. The ANOVA-test and Pearson product-moment correlation were used to test the hypotheses. Stepwise multiple regression was employed to determine which of the independent variables of the study are strong predictors of the KAP-level. The findings revealed that KAP-Ievel of both low and high-SES farmers on the technology of BPH control management had increased after the multi-media campaign. However, the multi-media approach of SEC had narrowed the KAP-gaps of these farmers. It was found that, therefore, the degree of equality with regards to the KAP-level in the Muda Irrigation Scheme area had increased. Organisational membership and paddy income were found to be positively related to KAP-level of the low-SES farmers before the campaign, while age was found to be negatively related to the KAP-level. Meanwhile, in the high-SES farmers groups before the campaign, the organisational membership was found to be positively related to their KAP-level.After the campaign, educational attainment, paddy income, organisational membership, contacts with change agent, cosmopoliteness, multi-media exposure, frequency of using, understanding level, usefulness of the multi-media messages, and farmers' perception on the multi-media approach of SEC were found to be positively related to the KAP-level of the low-SES farmers. Age and farmers' preference on the printed media, however, were found to be negatively related to KAP. In the high-SES groups, all the independent variables were found to be positively related except the farmer's preference on the printed media which was found to be negatively related to the KAP-level. The stepwise multiple regression analysis suggests that organisational membership is strong predictor of the KAP-level of the low and high-SES farmers before the campaign. However, the multi-media exposure, farmers' perception on the multi-media approach of SEC, and organisational memberships are the important predictors of the KAP-level of the farmers with low-SES after the campaign. The contacts with change agents, multi-media exposure, and organisational memberships were also found to be the important predictors of the KAP-level of the farmers in the high-SES group. It is recommended that, therefore, in order to increase the KAP-level of those two group of farmers, the task-force of SEC should pay attention to the above predictors.